Pengaruh Baby SPA, Lama Screen Time dan Kebisingan terhadap Kualitas Tidur Batita - Yunia Sari, Nunik Ike; Maringga, Estin Gita (Faletehan Health Journal, 2024)
Sleep problems were experienced by around 44.2% of babies in Indonesia. 72% of parents did not consider sleep disturbances as a problem of children’s growth and development, so it did not get maximum treatment. This study aims to determine the effect of baby SPA, screen time duration, and noise on the quality of children’s sleep. The research design was analytical with a cross-sectional study design. The research was conducted from October 1st, 2023 to November 30th, 2023 at Sun Baby SPA and Alodea Baby Care. The number of respondents was 80 mothers of toddlers who participated in the baby SPA. The sampling technique used was purposive sampling. The variables included baby SPA, screen time duration, noise, and child sleep quality. The data was collected using the Brief Infant Sleep Questionnaire and other specific data was filled out online through a Google form link. The data obtained were then analyzed multivariately using logistic regression. The results showed a significant relationship between baby SPA, screen time duration, and noise on child sleep quality (p<0.05). The logistic regression results showed that screen time duration had a greater influence on child sleep quality (p=0.018, OR=8.058). The duration of screen time must get special attention from parents since reducing screen time exposure in children affects the quality of children’s sleep quality and growth and development.